Implementasi Konsep Ergonomi pada Penggunaan Alat Tenun Tradisional Rumah Tenun Kampung Sabu - Selan, Rima N.; Tualaka, Theodora M. C.; Manu, Ariency Kale Ada (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
HIX symbolize human work from beginning to end. "X" is a variable for: design, manufacturing, test, and so on. “HI” symbolizes human integrated. Human Integrated System (HID) is a system designed with the capabilities and limitations possessed by humans so that the results of the design can increase effectiveness. Occupational diseases are caused by work and work attitudes. One of the occupational diseases of the spine is lower back pain, which arises due to a static position at work and is continuous. Every year 15%-45% of adults suffer from low back pain and generally occurs at the age of 35-55 years. The application of ergonomics is a design activity or redesign that is adapted to technological advances as well as anatomy, psychology, industrial medicine. The sitting position during the process of carrying out weaving activities which lasts a long time with a time of 8 hours per day, causes the sitting position to become less comfortable and results in complaints of pain in the back or spine. The ultimate goal of this study is to implement the concept of ergonomics in the use of traditional looms so as to reduce complaints of pain or spinal pain from weavers